Assays for estimating HIV incidence: updated global market assessment and estimated economic value. Issue 3 (22nd November 2017) - Morrison, Charles S; Homan, Rick; Mack, Natasha; Seepolmuang, Pairin; Averill, Megan; Taylor, Jamilah; Osborn, Jennifer; Dailey, Peter; Parkin, Neil; Ongarello, Stefano; Mastro, Timothy D
Abstract: Introduction: Accurate incidence estimates are needed to characterize the HIV epidemic and guide prevention efforts. HIV Incidence assays are cost‐effective laboratory assays that provide incidence estimates from cross‐sectional surveys. We conducted a global market assessment of HIV incidence assays under three market scenarios and estimated the economic value of improved incidence assays. Methods: We interviewed 27 stakeholders, and reviewed journal articles, working group proceedings, and manufacturers' sales figures. We determined HIV incidence assay use in 2014, and estimated use in 2015 to 2017 and in 5 to 10‐years under three market scenarios, as well as the cost of conducting national and key population surveys using an HIV incidence assay with improved performance. Results: Global 2014 HIV incidence assay use was 308, 900 tests, highest in Asia and mostly for case‐ and population‐based surveillance. Estimated 2015 to 2017 use was 94, 475 annually, with declines due to China and the United States discontinuing incidence assay use for domestic surveillance. Annual projected 5 to 10 year use under scenario 1 – no change in technology – was 94, 475. For scenario 2 – a moderately improved incidence assay – projected annual use was 286, 031. Projected annual use for scenario 3 – game‐changing technologies with an HIV incidence assay part of (a) standard confirmatory testing, and (b) standard rapid testing, were 500, 000 and 180 million, respectively. As HIV incidence assay precision increases, decreased sample sizes required for incidence estimation resulted in $5 to 23 million annual reductions in survey costs and easily offset the approximately $3 million required to develop a new assay. Conclusions: Improved HIV incidence assays could substantially reduce HIV incidence estimation costs. Continued development of HIV incidence assays with improved performance is required to realize these cost benefits.